Sistem Pendeteksi Gelombang Otak Berbasis Electroencephalogram (EEG) Pada Studi Kasus Anak Penderita Autisme - Gamaliel Saverius Siregar; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Brain is the important part as a control center, coordination and controling the human body. Inside the brain can be noticed that there are activity and abnormalities of the brain work. Every single person has activity or abnormalities brain work. It can happen to children with autism. Children who have an autistic symptoms occur due to distrubance of complex and variation of the brain function. A brain waves recorder or Elektroesefalogram can see and read the brain work activity. elektroesefalogram is a test that is used to know the electrical activity of the brain to detect whether there is a brain abnormality or not. This research designs a prototype EEG equipment especially to record children with autistic symptoms. The choosen participants in this research are chosen by seeing the result of CAST questionnaire that contains 37 questions. The recording in this research is used by using a particular sensor which is electrode, that is installed on the scalp and connected to computer/laptop. Using 4 electrodes in the lobes that are determined as a benchmark. The result of the recording can be displayed directly by MATLAB on a connected computer.Keywords : Autism, EEG, CAST, electrodes, Electroensephalogram, MATLAB.